2021
DOI: 10.1016/j.amsu.2021.102965
|View full text |Cite
|
Sign up to set email alerts
|

Study to estimate the average blood loss in different orthopedic procedures: A retrospective review

Abstract: Background In orthopedic surgery, bleeding is an inevitable side effect. The study's aim was to provide estimated blood loss values in various orthopedic procedures and take a step towards developing statistically reliable formulae. This can provide blood loss values in orthopedic surgery, which will be a very good tool for operative planning. Materials and methods We reviewed case notes of 282 patients in a UK based trauma center from December 2020 to March 2021,who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Tis correlated to a study done in Saudi Arabia that found no diference in the use of tourniquets in TKR surgeries [20]. Te use of tourniquets has largely been associated with lower levels of bleeding in patients intraoperatively [24], contrary to the results of our study. Some of the surgeries were associated with longer intraoperative duration, which might have ofset the mean Hb drop results.…”
Section: Advances In Orthopedicssupporting
confidence: 84%
“…Tis correlated to a study done in Saudi Arabia that found no diference in the use of tourniquets in TKR surgeries [20]. Te use of tourniquets has largely been associated with lower levels of bleeding in patients intraoperatively [24], contrary to the results of our study. Some of the surgeries were associated with longer intraoperative duration, which might have ofset the mean Hb drop results.…”
Section: Advances In Orthopedicssupporting
confidence: 84%